Ask Not For Whom the Law School Bell Tolls: Professor Tamanaha, Failing Law Schools, and (Mis)Diagnosing the Problem - Michael A. Olivas (Washington University Journal of Law & Policy, 2013)
It is a truth universally acknowledged that law faculty are in want of purpose. It takes a lot to get us riled, and even more to call us to the barricades. But the current state of financing legal education is just such a burning theater, and we all should be troubled by the fast- churning events. Because most of us went to law school during the Golden Age, which I situate as having ended in approximately 2005– 06, at the top of the application apex and the height of the modern- day job markets for law graduates, most of us are blissfully unaware of recent developments that literally threaten the enterprise. I write to discuss these many moving parts and to call us to action as a community, for threats to the universe of legal education will affect us all to our collective detriment and to that of our students. The real Cassandra, however, is Professor Brian Z. Tamanaha, whose apocalyptic book Failing Law Schools is a shrill call to arms, a substantial work of powerful charges and dire solutions, well-written and arriving at a crucial time in legal education, in the United States and worldwide. I believe he holds powerful diagnostic skills and has a storyteller’s narrative, but I believe his solutions are substantially wide of the mark, and would violate the code that remedial actions should, at the least, do no harm. If he were simply overstating issues or being a provocateur for the sheer sake of being one, as other critics have done, I would simply let him stew in his own juices. But his devastating critique has a number of accurate observations, ones I share, so laying out his arguments and his critical architecture is necessary to see how the analytic second step—his remedies—can be so wrong. Indeed, rather than merely noting his architectural framework, I will note the arithmetic of his remedies, and attempt to show why he should receive only partial credit for his math homework.
Keywords: legal education; law schools; failing law schools; tamanaha